2016
DOI: 10.1097/aud.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Binaural Hearing Ability With Bilateral Bone Conduction Stimulation in Subjects With Normal Hearing: Implications for Bone Conduction Hearing Aids

Abstract: The results confirm that binaural hearing processing with bilateral BC stimulation at the mastoid position is also present at the BCHA implant position. This indicates the ability for binaural hearing in patients with good cochlear function when using bilateral BCHAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…6 In a follow-up study, similar binaural benefits were demonstrated with bone conduction transducers placed at the clinical BAHD position. 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 In a follow-up study, similar binaural benefits were demonstrated with bone conduction transducers placed at the clinical BAHD position. 7 …”
Section: Discussionmentioning
confidence: 99%
“…perceiving the absolute position of a sound source), but perhaps the emergence of ITD-determined binaural disparities (i.e., “converted ILDs”) is sufficient for listeners to achieve binaural unmasking. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCDs rely on the transmission of vibrations through the skull bone and surrounding tissues rather than via conventional air conduction (AC) pathways. When a BC stimulus is applied at one location of the skull, both the cochleae are stimulated almost simultaneously, reducing the interaural separation and decreasing the ability to extract binaural cues (Zeitooni, Maki-Torkko, and Stenfelt 2016). Due to the crosstalk between both inner ears, a degradation of SRM compared to AC stimulation is expected under BC stimulation, as seen in Stenfelt and Zeitooni (2013), where SRM for bilateral BC stimulation was approximately half of that for AC in normal hearing individuals.…”
Section: Introductionmentioning
confidence: 99%